2010
DOI: 10.1007/s10452-010-9315-y
|View full text |Cite
|
Sign up to set email alerts
|

Hatching phenology, life history and egg bank size of fairy shrimp Branchipodopsis spp. (Branchiopoda, Crustacea) in relation to the ephemerality of their rock pool habitat

Abstract: In temporary aquatic habitats, permanence and the severe disturbance associated with desiccation are strong selective agents expected to lead to differentiation in life history strategies in populations experiencing different disturbance regimes. Besides optimal timing of hatching of dormant life stages, maturation and reproduction, pool inhabitants also benefit from the acquisition of reliable cues for the quality of the ambient environment. We investigated whether hatching patterns, life history characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
59
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 32 publications
5
59
1
Order By: Relevance
“…This experiment is a follow-up of a previous study in which the effect of salinity on the succession of permanent inhabitants of temporary wetlands was assessed during only one inundation cycle (Waterkeyn et al 2010). …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This experiment is a follow-up of a previous study in which the effect of salinity on the succession of permanent inhabitants of temporary wetlands was assessed during only one inundation cycle (Waterkeyn et al 2010). …”
mentioning
confidence: 99%
“…However, for this to be a successful survival strategy, species need to hatch fractionally corresponding with chances for successful recruitment (Cohen 1966;Brown and Venable 1986), grow in time to maturity, and produce sufficient numbers of dormant eggs to replenish the dormant egg bank to compensate for losses due to hatching and mortality. Under more saline conditions, freshwater organisms are unlikely to hatch optimally and to survive until reproduction (Nielsen and Brock 2009;Vanschoenwinkel et al 2010). Failure to reproduce (abortive hatching) during several consecutive seasons may cause depletion of the dormant egg bank and eventually extinction of the local populations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In both cases, the level of empirical evidence met Category II b . Studies of anostracans typically dealt with the timing of diapausing egg hatching and were most prevalent in Category III (Hildrew, 1985;Saiah & Perrin, 1990;Simovich & Hathaway, 1997;Dumont & Ali, 2004;Vanschoenwinkel et al, 2010), with a remarkable exception in Branchinecta sandiegonensis Fugate, 1993, for which hatching fractions in different populations were found to be optimal given their respective frequency patterns of pool filling, so that Category VI was reached (Philipi et al, 2001). Similarly in copepods, it has been found that the timing of diapausing egg production in Diaptomus sanguineus Forbes, 1876, is in close agreement with a simulation-derived evolutionary stable strategy, thus reaching the highest level of empirical evidence for a conservative bethedging trait (Category VI).…”
Section: Remarksmentioning
confidence: 99%